Adaptive plasticity in anuran metamorphosis: response of tadpoles of Polypedates maculatus (Anura: Rhacophoridae) to pond drying - Mogali, Santosh M.; Shanbhag, Bhagyashri A.; Saidapur, Srinivas K. (Phyllomedusa: Journal of Herpetology, 2023)
The influence of desiccation on metamorphic traits (larval duration and size at emergence) was studied in Polypedates maculatus under laboratory conditions. Gosner Stage 23 tadpoles were exposed to decreasing water levels (gradual or rapid) until the beginning of metamorphic climax (Stage 42). A control group was reared in constant water levels. Tadpoles reared in decreasing water levels reached the metamorphic climax earlier and metamorphosed at a smaller size than those reared in constant water levels. Further, tadpoles experiencing rapid depletion of water reached the metamorphic climax earlier and metamorphosed at a smaller size than those experiencing gradual depletion of water levels. Tadpoles of P. maculatus showed adaptive plasticity in metamorphosis to pond drying. Survival of tadpoles in treatments and the control was 100%. The study revealed that tadpoles of P. maculatus have plastic development in response to water levels; the trade-off between growth and development favors development, which results in early metamorphosis at a small size.